2008
DOI: 10.1002/9780470151808.sc01c06s5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Human Placental Fibroblasts

Abstract: The first human embryonic stem cell lines (hESCs) were derived using mouse embryonic fibroblasts as feeder cells. In attempts to replace mouse embryonic fibroblasts with feeders of human origin, irradiated human placental fibroblasts were successfully used as feeder cells for the derivation and propagation of hESCs. Here we describe a protocol for the isolation and expansion of fibroblasts from placental villous stroma. We include a description of placental architecture to provide the background for a stepwise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Human umbilical vein cells (HUVECs) and smooth muscle cells were purchased from Lonza. As previously described, human placental fibroblasts (HPF) (45) and trophoblast progenitor cells (TBPCs) (46,47) were isolated and cultured. Human foreskin fibroblasts (HFF) were isolated and propagated by conventional methods (48).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Human umbilical vein cells (HUVECs) and smooth muscle cells were purchased from Lonza. As previously described, human placental fibroblasts (HPF) (45) and trophoblast progenitor cells (TBPCs) (46,47) were isolated and cultured. Human foreskin fibroblasts (HFF) were isolated and propagated by conventional methods (48).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…With the aim of eliminating the xeno-contamination derived from MEFs, numerous studies have demonstrated the maintenance of hESCs on primary feeder cells from humans, such as adult skin fibroblasts [9] and placental fibroblasts [10]. Regardless of where the feeder cells are derived from, they are only viable for a few days; thus, the hESCs must be routinely transferred onto fresh feeder cells for continued culture.…”
Section: Introductionmentioning
confidence: 99%
“…JEG-3 (choriocarcinoma cell line), J774 (mouse macrophage-like cell line), and MDCK (Madin-Darby canine kidney) cells were purchased from ATCC (https://www.atcc.org/) and propagated according to the instructions of ATCC. Human first-trimester placental fibroblasts and human trophoblast progenitor cells (hTPCs) were a generous gift from Susan Fisher and were propagated and differentiated as previously described (45,46). Mixed glial cell cultures were generated from newborn mice and plated onto poly-D-lysine (Millipore)-coated plates as previously described (47).…”
mentioning
confidence: 99%